Components in Qualitative Research - Faridatul Jannah; Halimatus Sa`diyah; Desi Endang Maisuri (Penerbit Hellow Pustaka, 2025)
This study aims to develop new knowledge about the components of research, this study can reveal the truth scientifically with research methods, research methods as a planned, systematic, scientific, and rational way to reveal facts, this study aims to examine in depth as an approach in scientific research. The object of the research approach is the qualitative research component. While the method chosen by the author is literature, (library research). In this study, the researcher examines in depth the components of qualitative research. The results of the study indicate that the use of research components is able to solve and determine problems, determine the truth and become knowledge that is useful for human life.